2021
DOI: 10.1186/s12951-021-00942-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia adipose stem cell-derived exosomes promote high-quality healing of diabetic wound involves activation of PI3K/Akt pathways

Abstract: Refractory diabetic wounds can cause persistent inflammation and delayed healing due to hypoxia. Currently, no optimal solution is available. Exosomes of adipose stem cells (ADSCs-exo) may promote skin wound healing, however, molecular mechanisms remains mysterious. We found significantly enhanced survival and proliferation of adipose stem cells after hypoxia induction compared to normoxia. Here, we aimed to investigate if hypoxic adipose stem cells exosomes (HypADSCs-exo) participate in hypoxia adaptability a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 51 publications
2
96
0
Order By: Relevance
“…Compared to normoxia, miR-21-3p, miR-126-5p, miR-31-5p were significantly upregulated while miR-99b and miR-146-a were significantly downregulated in hypoxic exosomes derived from adipose stem cells. Hypoxic exosomes exhibited significantly better effects in promoting wound healing than normoxic exosomes when they were injected into diabetic mice ( 173 ). miR-125b was also upregulated by hypoxia in the exosomes from umbilical cord-derived mesenchymal stem cells (ucMSCs), such exosomes can be taken up by endothelial cells and promoted cell proliferation, migration, inhibited apoptosis, and accelerated wound healing by targeting and suppressing the tumor protein p53 inducible nuclear protein 1 (TP53INP1) ( 175 ).…”
Section: Hypoxic Exosomes In Non-malignant Disease From Different Sys...mentioning
confidence: 99%
“…Compared to normoxia, miR-21-3p, miR-126-5p, miR-31-5p were significantly upregulated while miR-99b and miR-146-a were significantly downregulated in hypoxic exosomes derived from adipose stem cells. Hypoxic exosomes exhibited significantly better effects in promoting wound healing than normoxic exosomes when they were injected into diabetic mice ( 173 ). miR-125b was also upregulated by hypoxia in the exosomes from umbilical cord-derived mesenchymal stem cells (ucMSCs), such exosomes can be taken up by endothelial cells and promoted cell proliferation, migration, inhibited apoptosis, and accelerated wound healing by targeting and suppressing the tumor protein p53 inducible nuclear protein 1 (TP53INP1) ( 175 ).…”
Section: Hypoxic Exosomes In Non-malignant Disease From Different Sys...mentioning
confidence: 99%
“…MSC-EXO exert beneficial effects via bioactive substances that include proteins, mRNAs, LncRNA and miRNAs. Notably, the substances in MSC-EXO are largely influenced by environmental stimuli that alters their biological effect [ 20 , 21 ]. Thus, optimizing MSC-EXO in vitro to enhance their therapeutic effects is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that miR-21 promoted ROS production through NOX2 regulation by the PI3K pathway in macrophages, which influenced the wound healing process ( Liechty et al, 2020 ). Additional studies have also demonstrated that miR-21 enhanced the migration and proliferation of the HaCaT cells and inhibited inflammation through PI3K/Akt signaling pathway, accelerating the wound healing process ( Liu et al, 2021 ; Wang et al, 2021 ; Yang et al, 2020 ). However, the specific mechanism by which miR-21 regulates the PI3K/Akt pathway remains poorly understood.…”
Section: Overview Of Mir-21mentioning
confidence: 99%